Does processing speed exert an influence on the special relationship of fluid and general intelligence?. (1st September 2018) - Schweizer, Karl; Troche, Stefan J.; Rammsayer, Thomas H.
Abstract: The paper investigates why the virtual correspondence of the ability component of fluid reasoning scores and general intelligence observed by Schweizer, Troche, and Rammsayer (2011) was not replicated by Lozano (2015). It is shown that the time limit of the scale used in the former study caused a speed effect that strengthened the relationship, whereas the scale used by Lozano (2015) that was considered as unspeeded did not cause such an effect. Modifying the statistical model to eliminate this effect resulted in similar estimates of the relationship between the ability component of fluid reasoning and general intelligence. Highlights: Identification of processing speed as source of structural distortion Revision of the relationship of reasoning and general intelligence Demonstration of the replicability of results of differential research Decomposition of reasoning scores into three components